The British Peace Movement in the Interwar Years - Richard Davis (Revue Française de Civilisation Britannique)
1918 was regarded by many observers at the time as marking the end of an era and the death of the old international order. Hopes for a peaceful future and a deep-rooted abhorrence of war as a means of settling international disputes were characteristic of large parts of British opinion in the interwar years. Pacifism, in its most general sense, was widely shared across British society. British decision makers shared this broadly felt revulsion against war. This was backed up by the purely rational calculation that Britain had nothing to gain from war and that its national interests would be best served by preserving international peace.These sentiments were channelled via a number of different peace movements which drew on various forms of socialist, humanist and Christian thought. While they all shared a common and broadly peaceful outlook there remained strikingly divergent approaches between what some historians such as A.J.P. Taylor and Martin Ceadel have termed the pacificists as opposed to the pacifists. While the former put forward a broadly peaceful policy the latter group remained opposed to all war on principle, to the point of adopting a policy of non-resistance. Over the course of the interwar years, with the heightened threat to international peace from the revisionist powers in Europe and the Far East, the tensions between the various peace movements became ever greater. At times, as for example during the Italo-Ethiopian war, the peace movement was able to mobilise a mass following that was able to exercise a significant pressure on decision makers. However, the anti-war sentiments expressed by movements such as the League of Nations Union and the Peace Pledge were in fact widely shared from within official circles. The more clear-cut pacifists however, who refused to support a policy of either rearmament or of collective security in the name of the League of Nations, had little input into policy making and their ideas and leaders were, for the most part, dismissed out of hand. By the time that war came in 1939, both sides of the peace movement had lost much, if not all, of their earlier enthusiasm and support in the country.